FATIGUE IN OLDER ADULTS WITH ACUTE LEUKEMIA DURING INITIAL CHEMOTHERAPY. (11th November 2018) - Bryant, A L; Gosselin, T; Coffman, E; Phillips, B; Fowler Gray, T; Knafl, G J; Reeve, B B
Abstract: There is limited research focused on patient reported fatigue symptom experiences in adults receiving treatment for acute leukemia. The purpose of this study was to prospectively examine fatigue in newly diagnosed adults with acute leukemia receiving induction chemotherapy. Weekly assessments captured fatigue using PROMIS measures. Data were analyzed using linear mixed modeling and adaptive regression modeling. Forty-nine adults with acute leukemia completed assessments from hospitalization through discharge. Mean age was 53 years, 18% minority, and majority had a diagnosis of AML (72%). Average length of stay was 34.8 (SD 14.0) days. Mean baseline fatigue (57.8; mean score in US population is 50 with SD 10) was not statistically significant but there were minimally important differences. Adults over 50 with acute leukemia experienced greater fatigue during hospitalization than those <50 years of age. Fatigue is a dose-limiting symptom of cancer therapy that warrants intervention.